Slower speed of blood pressure recovery after standing is associated with accelerated brain aging: Evidence from The Irish Longitudinal Study on Ageing (TILDA) - Afonso Shirsath, Morgana; Kenny, Rose; O'Connor, John; Newman, Louise; Knight, Silvin; Whelan, Robert; Meaney, James (My University, 2024)
Background: Impaired recovery of blood pressure (BP) in response to standing up is a prevalent condition in older individuals. We evaluated the relationship between the early recovery of hemodynamic responses to standing and brain health in adults over 50. Methods: Participants from The Irish Longitudinal Study on Ageing (TILDA) (n=411; age 67.6 ± 7.3 years; 53.4 % women) performed an active stand challenge while blood pressure and heart rate were continuously moni- tored. The recovery of these parameters was determined as the slope of the BP and HR response, following the initial drop/rise after standing. We have previously reported a novel and validated measure of brain ageing using MRI data, which measures the difference between biological brain age and chronological age, providing a brain- predicted age difference (brainPAD) score. Results: Slower recovery of systolic and diastolic BP was found to be significantly associated with higher brainPAD scores (i.e., biologically older brains), where a one-year increase in brainPAD was associated with a decrease of 0.02 mmHg/s and 0.01 mmHg/s in systolic and diastolic BP recovery, respectively, after standing. Heart rate (HR) recovery was not significantly associated with brainPAD score. Conclusion: These results demonstrate that slower systolic and diastolic BP recovery in the early phase after standing is associated with accelerated brain aging in older individuals. This suggests that the BP response to standing, measured using beat-to-beat monitoring, has the potential to be used as a marker of accelerated brain aging, relying on a simple procedure and devices that are easily accessible.
PUBLISHED
doi: 10.1016/j.cccb.2024.100212
Keywords: Active stand; Cerebral autoregulation; Orthostatic hypotension; Brain aging; Ageing; Neuroscience; Age related diseases; Ageing, memory and other cognitive processes; Epidemiology; Age-related disability; Chronic Health Condition